Factors associated with duration of breastfeeding in Bangladesh: evidence from Bangladesh demographic and health survey 2014 - Ummay Ayesha; A. S. M. A. Mamun; Md. Abu Sayem; Md. Golam Hossain (BMC, 2021)
Abstract Background Breastfeeding for optimum duration is one of the most effective ways to reduce infant morbidity and mortality and confirms expected growth and development of children. The aim of this study was to determine the effect of socio-demographic and anthropometric determinants on duration of breastfeeding (DB) among mothers in Bangladesh. Methods The data was extracted from the Bangladesh Demographic and Health Survey (BDHS)-2014. A total of 3541 married non-pregnant and currently non-breastfeeding Bangladeshi mothers in reproductive age who had at least one child aged 6-36 months were included in this study. Independent sample t-test and one-way analysis of variance (ANOVA) were used to find the significance difference in DB between two and more than two groups respectively. Multiple linear regression model was utilized to determine the effect of socio-economic, demographic, anthropometric and health related variables on DB. Results This study revealed that the mean and median of DB among Bangladeshi mothers were 18.91 (95% CI: 18.65-19.17) and 19.00 months respectively. Independent sample t-test and ANOVA showed that DB among Bangladeshi mothers was significantly influenced by (i) ANC visits, (ii) religion, (iii) mode of delivery, (iv) place of delivery, (v) parents' education, (vi) geographical location, (vii) mothers' occupation and (viii) household wealth quintile. Multiple regression analysis demonstrated that mothers' age, total number of children, mothers' age at first birth, ANC visits, mothers' occupation and geographical location were important predictors of DB. Conclusions Healthcare providers and decision makers can consider these findings to make plan for counseling of mothers and family members to promote optimum DB practice in first 2 years of baby's life.